Pengaruh Warna Lampu Celup Dalam Air Terhadap Hasil Tangkapan Bagan Tancap Di Perairan Kabupaten Bangka Tengah - feri feri yadi; Wahyu Adi; Eva Utami (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
The Submerged Light in the Water is one of the catching tools for fishermen with step-step charts. Research with trials of differences in the color of Lacuda's light was carried out in the waters of Tanjung Pura Village with the aim of getting better results. The purpose of this study was to analyze the effect of the color of the lights in the water on the catch on the live chart. The research was conducted in January 2019 in the waters of Tanjung Pura, Central Bangka Regency. The method used in this research is the fishing trial or experimental method of fishing and the statistical method used in this experiment is a randomized block design (RBD). The color of light lacuda that most influences the catch of the fixed chart is white lacuda with a catch of 184.63 kg, while treatment of yellow lacuda is 129.4 kg, treatment of blue lacuda is 109.25 kg, and treatment of lacuda with green color gets the lowest yields with a catch of 79.7 Kg.